(untitled) (Research, Society and Development, 2022)
Objective: a systematic review was carried out and the relevance of a natural class of secondary metabolites, the flavonoids, present in several species of the plant kingdom, such as apples, cabbage, grapes, onions and broccoli, was demonstrated, aiming at the possible development of future effective drugs against several diseases considered public health problems. Methodology: the identification of articles was based on research of scientific works published in PubMed, SciELO and Google Scholar. Articles were included that addressed the general concepts of flavonoids, focusing on their antioxidant activity, free radical activity, action of reactive oxygen species and function of vitamins C and E. Results and discussion: 31 articles, with varying results according to the clinical trials performed, their characteristics and specific objectives, demonstrating general characteristics of flavonoids and their main therapeutic applications. Conclusions: it was possible to observe the main characteristics of flavonoids such as their basic structure, their different classes and therapeutic applications, mainly their antioxidant activity.